Survival of HIV-positive patients starting antiretroviral therapy between 1996 and 2013: a collaborative analysis of cohort studies. Issue 8 (August 2017) - ,; Trickey, Adam; May, Margaret T; Vehreschild, Jorg-Janne; Obel, Niels; Gill, M John; Crane, Heidi M; Boesecke, Christoph; Patterson, Sophie; Grabar, Sophie; Cazanave, Charles; Cavassini, Matthias; et al.
Summary: Background: Health care for people living with HIV has improved substantially in the past two decades. Robust estimates of how these improvements have affected prognosis and life expectancy are of utmost importance to patients, clinicians, and health-care planners. We examined changes in 3 year survival and life expectancy of patients starting combination antiretroviral therapy (ART) between 1996 and 2013. Methods: We analysed data from 18 European and North American HIV-1 cohorts. Patients (aged ≥16 years) were eligible for this analysis if they had started ART with three or more drugs between 1996 and 2010 and had at least 3 years of potential follow-up. We estimated adjusted (for age, sex, AIDS, risk group, CD4 cell count, and HIV-1 RNA at start of ART) all-cause and cause-specific mortality hazard ratios (HRs) for the first year after ART initiation and the second and third years after ART initiation in four calendar periods (1996–99, 2000–03 [comparator], 2004–07, 2008–10). We estimated life expectancy by calendar period of initiation of ART. Findings: 88 504 patients were included in our analyses, of whom 2106 died during the first year of ART and 2302 died during the second or third year of ART. Patients starting ART in 2008–10 had lower all-cause mortality in the first year after ART initiation than did patients starting ART in 2000–03 (adjusted HR 0·71, 95% CI 0·61–0·83). All-cause mortality in the second and third years after initiation of ART was also lower in patients who started ART in 2008–10 than in those who started in 2000–03 (0·57, 0·49–0·67); this decrease was not fully explained by viral load and CD4 cell count at 1 year. Rates of non-AIDS deaths were lower in patients who started ART in 2008–10 ( vs 2000–03) in the first year (0·48, 0·34–0·67) and second and third years (0·29, 0·21–0·40) after initiation of ART. Between 1996 and 2010, life expectancy in 20-year-old patients starting ART increased by about 9 years in women and 10 years in men. Interpretation: Even in the late ART era, survival during the first 3 years of ART continues to improve, which probably reflects transition to less toxic antiretroviral drugs, improved adherence, prophylactic measures, and management of comorbidity. Prognostic models and life expectancy estimates should be updated to account for these improvements. Funding: UK Medical Research Council, UK Department for International Development, EU EDCTP2 programme.